Response of the intravenous versus oral antibiotic regimen in brucellosis bacteremia. - Imran Nazir; Mohammed A Al-Matrafi; Fozya Bashir Bashal; Nouf Alsahaf; Ahmed Farouk Aboelazm; Waleed Amasaib (Journal of University Medical & Dental College, 2024)
BACKGROUND AND OBJECTIVE: More than 500,000 new cases are reported globally annually.  The World Health Organization recommends doxycycline with rifampicin or an aminoglycoside for brucellosis bacteremia. Some experts prefer to use doxycycline and rifampicin. We aimed to observe the response rate of intravenous versus oral anti-brucella therapy regimens in brucellosis bacteremia patients and compare the frequency of side effects and complications in both groups.METHODOLOGY: This observational study included adult brucellosis bacteremia patients treated in a hospital in Makkah, KSA for four years. According to the method of treatment (oral versus IV antibiotics), patients were grouped into two categories. Following the treatment, all these patients’ records were evaluated. The negative blood culture was the primary endpoint whereas complications and all-cause mortality were secondary endpoints. The chi-square test, Fisher's exact test, and Mann-Whitney U test were applied accordingly to analyze the two groups’ characteristics.RESULTS: A total of 93 cases were enrolled, the majority were males i.e., 64 (68.8%); with a mean age group (44.33 ±19.22 years). In total, 37 (39.8%) of patients were given IV regimens and the remaining 56 (60.2%) of patients were given oral regimens. Follow-up negative blood culture after 4 weeks was 90.3% (n = 84). The recovery rate was 93.5% (n = 87). No death was reported over this period. No difference was observed (P-value 0.309) between the oral and IV treatment regimens regarding the blood culture negativity.CONCLUSION: Oral doxycycline-rifampicin (DR) and IV gentamicin-doxycycline-rifampicin (GDR) regimens have similar response rates in bacteremia brucellosis.